PENINGKATAN KESADARAN TENTANG RISIKO KEHAMILAN USIA REMAJA PADA PENGUNJUNG POLIKLINIK BAGIAN KANDUNGAN DAN KEBIDANAN RS SUMBER WARAS JAKARTA BARAT - Dewi, Andriana Kumala; Syilvia Cendy Enike,; Kasvana,; Cindy Yusliani, (Jurnal Bakti Masyarakat Indonesia, 2025)
Adolescent pregnancy is a reproductive health issue with broad consequences—physically, psychologically, and socially. This Community Engagement Program aimed to raise awareness among visitors of the Obstetrics and Gynecology Outpatient Clinic at Sumber Waras Hospital regarding the risks of early-age pregnancy. The activity was carried out through interactive educational counseling led by an obstetrics and gynecology specialist, followed by an open discussion session and the distribution of educational leaflets. The materials covered medical, psychological, and social impacts of teenage pregnancy, using a communicative and participatory approach. Evaluation was conducted descriptively, based on participant observation and documentation of engagement levels. The results indicated an improvement in participants' understanding, as reflected in active participation during discussions and positive feedback on the educational content. This program also produced tangible outputs such as a scientific article and educational materials for sustained use within the hospital. In addition, the program involved medical students (general clinical rotation) from the Faculty of Medicine at Tarumanagara University (FK UNTAR), providing them with valuable experience in promotive and preventive competencies in reproductive health. Overall, this initiative is expected to serve as a strategic step in reducing adolescent pregnancy rates through well-targeted education.